Physical and Mental Health Problems among Elderly in Selected Geriatric Homes of Makawanpur District - Bajracharya, Anu; Kharel, Sagun; Karkheti, Ashwin; Paudel, Indira Adhikari (Nepal Journal of Health Sciences, 2023)
Introduction: With the advancing age, there comes increased risk of medical illness, psychiatric problems and use of medication, all of which may adversely impact on the physical and mental health status of the elderly. Studies investigating physical and mental health problems among elderly in geriatric homes are rare in Nepal. Objective: The objective of this study was to assess the physical and mental health problems among elderly of selected geriatric homes of Makawanpur district. Methods: A descriptive cross-sectional research design was carried out among the old people of three geriatric homes of Makawanpur district. Data was collected through structured interview schedule consisting of demographic, medical history and social information including geriatric depression scale and geriatric anxiety scale. Data was analyzed by using SPSS version 16 using descriptive statics. Result: A total of 84 respondents in the study, 90.2% of the respondents having physical symptoms. Among them pain (90.2%), weakness (26.6%), fatigue (18.3%) were the common symptoms. Furthermore, 76.8% of elderly were having physical health problems and more common problems were hypertension (55.55%), Diabetes (33.33%) and asthma (25.57%). Similarly 36.4% of the respondents had depression and 39% have anxiety. Conclusion: Based on the findings, it is concluded that hypertension, diabetes and asthma were more common physical problems and depression, anxiety were more common mental health problems among old people. Therefore, provision of regular health check-up program for elders can enhance their physical as well as mental health so that complications can be prevented in time.